Efeitos da microinjeção de metilatropina nos núcleos ventromediais do hipotálamo (hvm) de ratos durante o exercício - Nilo Resende Viana Lima (2000)
The aim of present study was evaluate the participation of cholinergicreceptors of hypothalamic ventromedial nuclei (VMH) in the adjustments of metabolism, cardiovascular system and body temperature in untrainedexercising rats until fatigue. Male Wistar rats (250-300g, body weight0 were anesthetized with thionembutal (30 mg.kg-1, b.wt., i.p.) and bilateral brain cannula was implanted for 0.2 L of methylatropine (5 x 10-9 mol) or NaCl (0.15 M) injection into the VMH. The animals were fitted with chronic jugular catheters for blood sampling and cannula into the aorta for blood presseure measurements. Body temperature was measured with intraperitoneal radiotelemeters. Exercise was performed on a motor-driven treadmill until exhaustion and the intensity of exercise was 80% of VO2max , determined previously. Our results show that the cholinergic blockade of hypothalamic ventromedial nuclei of untrained rats reduced in 50% the maximal capacity for exercise indicating that these neurons modulate physical performance of rats running at 80 % of VO2max . Furthermore, the cholinergic blockade of VMH anticipated in 50% the exercise induced increase of glucose and lactate levels and increased the blood pressure and heart rate values. In addition, the blockade of VMH with methylatropine attenuated the exercise-induced the rate increase in body temperature. Our data suggest that cholinergic receptors of ventromedial nuclei participate in the modulation of peripheral sympathetic activity during exercise